Nano-Metal Stability and its Outcomes - Vigdorowitsch, Michael (Journal of Applied Solution Chemistry and Modeling, 2022)
A thermodynamics-based approach to determining stability conditions for metallic nano-ensembles is proposed. It is related to that [ultra-]dispersing the substance leads to changes in thermodynamic potentials (TPs) compared to those of a massive crystal of the same nature. This dimensional phenomenon consists of two components. Among those are a reduction of TPs due to vacancy-related effects and an increase of TPs due to the surface tension effect. Even linear, exponential, and normal distributions of particles on their size in the ensemble have been considered. The resulting equations have been applied to the nano-ensembles of either In or Au particles. The presence of ultra-small particles in an ensemble makes the vacancy-related effect more apparent than the surface tension effect, promoting system stability. With the decrease in the number of ultra-small particles, the vacancy-related effect drastically diminishes and can yield to the surface tension effect, thereby leading to the loss of stability.